Knadungan Unsur Fluor pada Email Gigi TetaP Muda dengan Tumpatan Semen Ionomer Kaca Viskositas Tinggi - Ririen Titi Yuliarti; Ismu Suharsono Suwelo; Sri Harini Soemartono (Faculty of Dentistry, Universitas Indonesia, 2013)
The purpose of this study was to determine the fluoride content differences in enamel of immature teeth with Glass Ionomer Cement Fuji IX and Ketac Molar filling.The subject for this study was 21 immature premolars teeth, and each tooth divided into 2 parts. The first part filled with Fuji IX (Fuji IX ART, GC) and the second part filled with Ketac Molar (KetacMolar ART, MI, 3M ESPE), so the samples were 21 Energy Dispersive X-Ray Spectrophotometry analysis of Fuji IX and 21 Energy Dispersive X-Ray Spectrophotometry analysis of Ketac molar. The measurement was done to the fluoride content in enamel of immature teeth using Energy Dispersive X-Ray Spectrophotometry in percentage.This study using t-test, exhibited differences but no significant from the percentage of delta the fluoride content in enamel of immature teeth with Fuji IX and Ketac Molar filling (t=1,953 p > 0.05). DOI: 10.14693/jdi.v15i2.74